Thrombomodulin‐dependent protein C activation is required for mitochondrial function and myelination in the central nervous system. (20th October 2016) - Wolter, J.; Schild, L.; Bock, F.; Hellwig, A.; Gadi, I.; Al‐Dabet, M. M.; Ranjan, S.; Rönicke, R.; Nawroth, P. P.; Petersen, K.‐U.; Mawrin, C.; Shahzad, K.; et al.
Abstract : Essentials The role of protein C (PC) activation in experimental autoimmune encephalitis (EAE) is unknown. PC activation is required for mitochondrial function in the central nervous system. Impaired PC activation aggravates EAE, which can be compensated for by soluble thrombomodulin. Protection of myelin by activated PC or solulin is partially independent of immune‐modulation. Summary: Background: Studies with human samples and in rodents established a function of coagulation proteases in neuro‐inflammatory demyelinating diseases (e.g. in multiple sclerosis [MS] and experimental autoimmune encephalitis [EAE]). Surprisingly, approaches to increase activated protein C (aPC) plasma levels as well as antibody‐mediated inhibition of PC/aPC ameliorated EAE in mice. Hence, the role of aPC generation in demyelinating diseases and potential mechanisms involved remain controversial. Furthermore, it is not known whether loss of aPC has pathological consequences at baseline (e.g. in the absence of disease). Objective: To explore the role of thrombomodulin (TM)‐dependent aPC generation at baseline and in immunological and non‐immunological demyelinating disease models. Methods: Myelination and reactive oxygen species (ROS) generation were evaluated in mice with genetically reduced TM‐mediated protein C activation (TM P ro/Pro ) and in wild‐type (WT) mice under control conditions or following induction of EAE. Non‐immunological demyelination was analyzed in the cuprizone‐diet model. Results: Impaired TM‐dependent aPC generation already disturbs myelination and mitochondrial function at baseline. This basal phenotype is linked with increased mitochondrial ROS and aggravates EAE. Reducing mitochondrial ROS (p66 Shc deficiency), restoring aPC plasma levels or injecting soluble TM (solulin) ameliorates EAE in TM P ro/Pro mice. Soluble TM additionally conveyed protection in WT‐EAE mice. Furthermore, soluble TM dampened demyelination in the cuprizone‐diet model, demonstrating that its myelin‐protective effect is partially independent of an immune‐driven process. Conclusion: These results uncover a novel physiological function of TM‐dependent aPC generation within the CNS. Loss of TM‐dependent aPC generation causes a neurological defect in healthy mice and aggravates EAE, which can be therapeutically corrected.